From workplace attachment to commuter satisfaction before and after a workplace relocation. (May 2020) - Gerber, Philippe; El-Geneidy, Ahmed; Manaugh, Kevin; Lord, Sébastien
Highlights: A large retrospective survey was designed to assess travel behaviors before / after a workplace relocation. Transitions in commuter satisfaction was assessed using a multinomial logistic model. The effect of travel modes attitudes on commuter satisfaction is confirmed, before and after a workplace relocation. Workplace satisfaction and workplace attachment have significant impact on commuter satisfaction. The perception of changes in travel time is an important factor in commuting satisfaction changes. The consideration of 'activity places' proves useful in explaining the commuting satisfaction. Abstract: While attention has been paid to travel satisfaction studies during the last decade, less research has investigated the relationship between the influence of a sense of place – and more particularly the psycho-environmental concepts of workplace attachment and workplace satisfaction – and commuting satisfaction. Using a retrospective survey, this paper focuses on the relocation of a workplace within the city of Montréal (Canada); the McGill University Healthcare Centre. It examines the motivations and barriers involved in the evolution of commuting characteristics, using the theoretical framework of mobility biographies. The empirical analysis includes a large dataset of independent variables, applying a multinomial logistic model in order to explain the transition of the employees' commuting satisfaction. With regard to the measurement of change in commuting satisfaction, the findings confirm the role of attitudes, while taking into account the contextual differences before and after relocation. The change in travel time is found to be an important factor in the evolution of commuter satisfaction, whereby reduced commuting time improves satisfaction, as expected. In addition, the more an employee is attached to the new workplace, the more the commuting satisfaction will increase. The results provide further evidence that the meaning of the workplace goes beyond a location or a space, and opens up new avenues for research in travel behavior.